Essentials of soil mechanics and foundations basic geotechnics - McCarthy, David F. (Harlow Pearson, 2014)
For courses in Soil Mechanics and Foundations. Essentials of Soil Mechanics and Foundations: Basic Geotechnics, Seventh Edition, provides a clear, detailed presentation of soil mechanics: the background and basics, the engineering properties and behavior of soil deposits, and the application of soil mechanics theories. Appropriate for soil mechanics courses in engineering, architectural and construction-related programs, this new edition features a separate chapter on earthquakes, a more logical organization, and new material relating to pile foundations design and construction and soil
Keywords: Geotechnik; Gründung -- Bauwesen; Bodenmechanik